DESIGNING A LABORATORY STAND FOR TESTING IMPACT RESISTANCE OF PLASTIC FILMS BY FREE-FALLING DART DROP ACCORDING ASTM D1709 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this article, the process of designing a laboratory stand for testing impact resistance of plastic films using free-falling dart drop method according to ASTM D1709, type A will be followed. It will be analyzed the all stages of designing-synthesis of project solutions, analysis and optimization, assessment and presentation of tasks. The purpose of the article is to create a designing basis for the variable design of impact resistance stands to be used in the design of non-standardized laboratory equipment.